Analysing The Determinants Of Financial Inclusion In The Informal Sector: A Regression-Based Approach - Priyanka Mehta; Dr. Vijay Pithadia (Educational Administration: Theory and Practice, 2024)
This study investigates the key determinants of financial inclusion among individuals working in the informal sector, with a specific focus on access to financial services and the usage of digital financial platforms. Data were collected from 255 respondents in Rajkot city using a structured questionnaire based on a five-point Likert scale. The study applies two separate multiple regression models to examine the influence of socio-economic variables on financial access and digital financial service usage. The findings indicate that education, employment type, and income significantly influence access to financial services, while digital literacy, digital platform trust and smartphone ownership are powerful indicators of the use of digital financial services. Interestingly, income shows a negative coefficient in the access model, possibly reflecting hidden complexities in financial behaviour. The study highlights the growing importance of digital readiness in enhancing financial inclusion within low-income and informally employed populations. The results underscore the need for targeted interventions such as financial education programs and improved digital infrastructure to bridge the inclusion gap. This research contributes to the existing literature by offering a dual perspective on traditional and digital financial inclusion and provides evidence-based insights for policymakers and financial institutions aiming to expand inclusive financial ecosystems.